Priorities for Biotechnology Research in Zimbabwe - Chikwamba, R. (International Service for National Agricultural Research, 2001)
The importance of agriculture to the Zimbabwean economy cannot be overemphasized. Agriculture (including forestry) contributes between 13% and 15% to GDP (Statistical Bulletin, 1994). It is an important foreign currency earner (especially during the decade from 1981 to 1991 when it contributed on average 48% to foreign currency earnings). It provides food for the rural and urban population, jobs for 35% of the employed population, while 75% of the rural population (65% of the total population) derive their livelihood from farming. The manufacturing sector obtains 60% of its raw materials from the agricultural sector. The sector is also a vital market for goods and services such as farm machinery, fertilizer, chemicals and transport. The agricultural sector has reached such a high level of development that Zimbabwe is one of the few countries in sub-Saharan Africa which is self-sufficient in food requirements. In normal years, substantial amounts of sugar, tobacco, maize and meat products are exported. The Zimbabwean economy is characterized by dualism, with a small commercial and industrial sector on the one hand, and a peasant economy with more than 65% of the population involved in it on the other. (Central Statistic Office, 1992 Census) the commercial and industrial sectors are more developed, with established enterprises running in the fields of agriculture, mining, commerce and manufacturing.